1995
DOI: 10.1016/s0022-5223(95)70282-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pulmonary and aortic homografts for right ventricular outflow tract reconstruction

Abstract: To determine late patient outcome and homograft durability, we reviewed 326 patients who received aortic (n = 230) or pulmonary (n = 118) cryopreserved homografts for right ventricular outflow reconstruction between January 1985 and October 1993. Patient survival, including operative mortality, 5 years after the operation was similar between the two groups (pulmonary homograft 86%, aortic homograft 80%; p = not significant by log-rank test). However, 5-year freedom from homograft failure was significantly bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
2
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(119 citation statements)
references
References 31 publications
4
107
2
6
Order By: Relevance
“…12 Since then, several studies have shown an improvement in survival rates, ranging from 81% to 94% at 3 years after surgery. 20,21 The results from the present study showed a cumulative 22 In addition, Bull et al pointed out the following significant risk factors for death: numerous postoperative complications, severe associated anomalies, few operations before conduit repair, and previous BlalockHanlon procedure. 15 Multivariate analysis of the data from the present patients revealed 2 risk factors: homograft replacement and the use of ePTFE.…”
Section: Discussionmentioning
confidence: 50%
“…12 Since then, several studies have shown an improvement in survival rates, ranging from 81% to 94% at 3 years after surgery. 20,21 The results from the present study showed a cumulative 22 In addition, Bull et al pointed out the following significant risk factors for death: numerous postoperative complications, severe associated anomalies, few operations before conduit repair, and previous BlalockHanlon procedure. 15 Multivariate analysis of the data from the present patients revealed 2 risk factors: homograft replacement and the use of ePTFE.…”
Section: Discussionmentioning
confidence: 50%
“…Forbess et al 19 , Bando et al 9 and Dearanie et al 4 found a higher failure rate of the homograft associated to the cardiopathies as truncus arteriosus, transposition of the great arteries with pulmonary stenosis and double exit pathway from the right ventricle; however, in this study, there was no homograft durability correlation with the type of cardiopathy.…”
Section: Graph 2 -Relation Of the Z Score Value Of The Pulmonary Valvcontrasting
confidence: 49%
“…The option of this service for the use of the pulmonary homograft, in such position, is based on studies that show that the aortic homograft in pulmonary position presents higher index of calcification due to its composition rich in elastin [4][5][6][7][8][9][10][11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zmiany degeneracyjne zachodzą szybciej w homograftach aortalnych niż w płuc-nych, a procesy wapnienia są bardziej nasilone [8,9]. Podjęto próbę przeznaczyniowego wszczepienia zastawki płuc-nej u pacjenta z bardzo zwapniałym homograftem, który -patrząc na obraz radiologiczny oraz retrospektywnie po usunięciu operacyjnym -można nazwać analogicznie do porcelanowej aorty "porcelanowym" homograftem aortalnym.…”
Section: Dyskusjaunclassified